The Effects of Flexibility in Employee Skills, Employee Behaviors, and Human Resource Practices on Firm Performance - Bhattacharya, Mousumi; Gibson, Donald E.; Doty, D. Harold (Journal of Management, 2005)
The components of human resource (HR) flexibility and their potential relationship to firm performance have not been empirically examined. The authors hypothesize that flexibility of employee skills, employee behaviors, and HR practices represent critical subdimensions of HR flexibility and are related to superior firm performance. Results based on perceptual measures of HR flexibility and accounting measures of firm performance support this prediction. Whereas skill, behavior, and HR practice flexibility are significantly associated with an index of firm financial performance, the authors find that only skill flexibility contributes to cost-efficiency.